Perinatal Experiences of Asian American Women During COVID-19. Issue 2 (March 2022) - Goyal, Deepika; Han, Meekyung; Feldman-Schwartz, Talia; Le, Huynh-Nhu
Abstract: Purpose: To explore the wellbeing, pregnancy, childbirth, and postpartum experiences of Asian American women who gave birth during the COVID-19 pandemic. Study Design: Qualitative exploratory design. Methods: Using convenience and snowball sampling, we recruited Asian American women who gave birth during the COVID-19 pandemic via social media. Participants completed sociodemographic and depressive symptom questionnaires and took part in a virtual semistructured interview where they were asked to describe their pregnancy, birth, and postpartum experiences in the midst of the COVID-19 pandemic. Qualitative content analysis methods were used to identify themes from participant narratives. Results: Thirty-eight Asian American women representing several racial ethnic subgroups (Asian Indian, Chinese, Filipino, Hmong, Laotian, Vietnamese) participated in our study. Participants were on average 34 ( SD = 3.5) years of age; the majority were married and lived in California. At the time of data collection, participants were 3.7 ( SD = 2.07) months postpartum and 5.3 to 10.5 months into the COVID-19 pandemic. Qualitative content analysis revealed two main themes: 1) unexpected perinatal journey, and 2) the emotional and psychological consequences of COVID-19. Clinical Implications: Our findings are not unique to Asian American women, but they offer insight for nurses taking care of all childbearing women. Nurses can provide individually tailored anticipatory guidance to help women navigate perinatal changes and manage expectations during future public health crises. Nurses can also encourage and help perinatal women identify ways to increase their own social support networks during the pregnancy and postpartum period. Abstract : Asian American women shared their experiences of being pregnant and giving birth during the COVID-19 pandemic. Like other new mothers in the United States, Asian American mothers reported that perinatal care during the pandemic was stressful and difficult. They were disappointed and sad about the aspects of childbirth they felt they had missed and at times overwhelmed by the unexpected reality of parenting a newborn in isolation.